Comparing Coping Styles Between Patients With Cancer and Healthy People - Sayede Tahere Taheri Otaghsara; Tahere Khaleghdoost Mohammadi; Faride Hasavari; Ehsan Kazem Nezhad Leyli (Guilan University of Medical Sciences, 2018)
Introduction: Cancer is one of the most important health problems of present times. Evidence suggests that stress and lack of proper coping styles can play a role in the onset and progression of cancer. Objective: This paper aims to compare the coping styles of cancer patients referring to a medical educational and healthy individuals in Rasht City. Materials and Methods: An analytical cross-sectional study was conducted with 77 cancer patients and 77 healthy individuals in selected hospitals of the Guilan University of Medical Sciences during 2014-2015 with the convenience sampling method. Data was collected through questionnaires consisting of individual and clinical variables, and The Folkman and Lazarus coping strategies. Data were statistically analyzed using descriptive statistics (mean, standard deviation, and frequency) and inferential statistics (the Chi-square, the Independent t test, Mann-Whitney, and regression analysis). Results: The subscales of seeking social support (P=0.047), accepting responsibility (P=0.004), rational problem solving (P=0.003), avoidance (P=0.012), and income level (P=0.023) were the factors associated with the coping style of cancer patients. In addition, cancer patients used the avoidance strategy more than others to deal with their problems (OR=4.3, P=0.019). Conclusion: Nurses can benefit from such studies to design educational, prevention and screening programs. We recommend that educational programs be developed and the patients be trained in using problem-focused styles in dealing with stress and life-threatening situations.